Association between sleep stages and hunger scores in 36 children. Issue 5 (27th August 2015) - Arun, R.; Pina, P.; Rubin, D.; Erichsen, D.
Summary: Background: Childhood obesity is a growing health challenge. Recent studies show that children with late bedtime and late awakening are more obese independent of total sleep time. In adolescents and adults, a delayed sleep phase has been associated with higher caloric intake. Furthermore, an adult study showed a positive correlation between REM sleep and energy balance. This relationship has not been demonstrated in children. However, it may be important as a delayed sleep phase would increase the proportion of REM sleep. Objectives: This study investigated the relationship between hunger score and sleep physiology in a paediatric population. Methods: Thirty‐six patients referred for a polysomnogram for suspected obstructive sleep apnoea were enrolled in the study. Sleep stages were recorded as part of the polysomnogram. Hunger scores were obtained using a visual analogue scale. Mean age was 9.6 ± 3.5 years. Results: Mean hunger scores were 2.07 ± 2.78. Hunger scores were positively correlated with percentage of total rapid eye movement (REM) sleep (r = 0.438, P < 0.01) and REM sleep duration in minutes (r = 0.471, P < 0.05). Percentage slow wave sleep (SWS) was negatively correlated with hunger score (r = −0.360, P < 0.05). There were no correlations between age, sex, body mass index percentiles, apnoea–hypopnoea index, total sleep time, sleep efficiency, sleep onset latency, stage 2 sleep duration and hunger scores. Conclusions: These findings suggest that delayed bedtime, which increases the proportion of REM sleep and decreases the proportion of SWS, results in higher hunger levels in children.